Factors influencing child maltreatment survivor interventions in Asia: Scoping review - Urang, Yudi Sampe; Karitas, Chionia; Puspita, Fitriana Ayu; Nugroho, Agustinus Budi (University of Muhammadiyah Malang, 2025)
Child maltreatment is a serious global issue that has long-term impacts on children's physical and mental health. In Asia, cultural, social, and economic variations affect the way interventions are conducted, so understanding the factors that influence interventions is crucial for effective treatment of these cases. This study aims to identify factors that influence interventions for survivors of child maltreatment in Asia. This systematic review was conducted by analyzing relevant literature using PubMed, GARUDA, Science Direct, and SpringrLink databases, with a total of 2,859 articles. Through a screening process based on predetermined inclusion and exclusion criteria, a total of eight articles were analyzed. The results showed that there are several factors that influence child maltreatment survivor interventions in Asia, including family, social, economic, health and social support. This study provides recommendations for policy makers and practitioners to design evidence-based intervention programs to reduce the incidence of child maltreatment and improve child well-being in the Asian region.